Correlation of serum IGF-1, AGEs and their receptors with the risk of colorectal cancer in patients with type 2 diabetes mellitus - Chen, Zeng; Hong, Qiao (Frontiers in Oncology, 2023)
BACKGROUND: According to epidemiological evidence, people with type 2 diabetes mellitus (T2DM) have a higher risk of developing colorectal cancer. OBJECTIVE: To examine the relationship between colorectal cancer (CRC) and serum levels of IGF-1, IGF-1R, sRAGE, AGE and RAGE in patients with type 2 diabetes. METHODS: One hundred forty-eight patients hospitalized in the Second Hospital of Harbin Medical University from July 2021 to July 2022 were enrolled and divided into experimental and control groups. There were 106 patients in the experimental group, including 75 patients with CRC and 31 patients with CRC+T2DM; the control group comprised 42 patients with T2DM. Circulating levels of IGF-1, IGF-1R, AGEs, RAGE, and sRAGE in the serum of the patients were measured using Enzyme-Linked Immunosorbnent Assay （ELISA） kits. RESULTS: Serum AGE, RAGE, IGF-1, and IGF-1R levels were higher in the CRC and CRC+T2DM groups than in the T2DM group, but the serum sRAGE concentrations in these groups were lower than those in the T2DM group (P < 0.05). Serum AGE, RAGE, sRAGE, IGF1, and IGF1R levels were higher in the CRC+T2DM group than in the CRC group (P < 0.05). In CRC+T2DM patients, serum AGEs were correlated with age (p = 0.027), and the serum AGE levels in these groups were positively correlated with RAGE and IGF-1 levels (p < 0.001) and negatively correlated with sRAGE and IGF-1R levels (p < 0.001). After correcting for confounding factors based on logistic multiple regression analysis, the effects of age, serum IGF-1 and IGF-1R on the development of CRC in patients with T2DM were statistically significant (p<0.05). CONCLUSION: Serum IGF-1 and IGF-1R levels independently influenced the development of CRC in patients with T2DM. Furthermore, IGF-1 and IGF-1R were correlated with AGEs in CRC patients who also had T2DM, suggesting that AGEs may influence the development of CRC in T2DM patients. These findings suggest that we may be able to lower the risk of CRC in the clinic by regulating AGEs through the regulation of blood glucose levels, which will affect IGF-1 and its receptors. Keywords: Type 2 diabetes, Colorectal cancer, IGF-1, IGF-1R, AGEs，RAGE, sRAGE